Efektivitas âSentilanâ Politis Pemerintahan Obama terhadap Standard and Poors - Simanjuntak, Mandohar B.B. (Jurnal Ilmiah Hubungan Internasional, 2013)
Abstract: The Government of the United States under Barrack Obama has sued Standard and Poors, arating agency, for their alleged act of deceiving investors. In this article, the writer tries to analyse threeresearch points. Firstly, the writer tries to probe the common characteristics of rating agencies ingiving investment performance analyses; secondly, to investigate whether the alleged misguiding hasstirred cases made public by the media; and finally, to see whether this case has another standpoint thatis quite effective economically and politically. The research done by the writer has revealed that theirrational approach employed by Standard and Poors in producing the performance reports is bothcommonly and usually done by other rating agencies in the industry. Furthermore, the media surveyhas shown that the legal action is not entirely baseless because there are cases sprung from the motionfuelled by the media. However, interestingly the conclusion from this research shows that this case hasanother dimension âa political dimension âbecause from a political perspective we can infer âthesecondâ reading that shows that this legal motion is actually a political âpinchâ whose purpose is moreof deterring than of penalising the company to pay for the damage caused by their investmentperformance reports.Keywords : rating agencies, irrationality, âthe second readingâ, deterring effect